Optimizing Freight Train Operations A Case Study of Junction Planning at JIIPE - Widyastuti, Hera; Ikhwan, Maylana (Journal of Civil Engineering, 2025)
Train scheduling is a fundamental aspect of efficientcy railway operations, in general Ttrain scheduling explain iat train timetable. In the pursuit of enhancing railway utilization for freight transport, the Indonesian government has implemented policies, including the integration of the railroad with JIIPE (Java Integrated Industrial and Ports Estate) along the main line of the North Java Railroad (PP 71 2021). However, the growing number of trains originating from the junction poses challenges to existing schedules, particularly impacting the Surabaya Pasarturi-Bojonegoro railroad segment. This study aims to calculate train scheduling based on headway and capacity, proposing adjustments to the departure frequency at Duduk Station in line with the train timetable (Gapeka) 2021 for the Surabaya Pasarturi-Bojonegoro Segment 12 of 17 alternative trains per day west direction  and 18 of 21 alternative trains per day east direction. It is essential to note that this proposed frequency exceeds theoretical capacity, emphasizing the need for careful planning of additional trains within the constraints of capacity theory to maintain operational efficiency.